HUBUNGAN AKTIVITAS FISIK DENGAN OBESITAS PADA ANAK SEKOLAH DASAR N 1 BENGKALIS TAHUN 2017 - Nuranisa Nuranisa; Albiner Siagian (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Abstract: WHO states obesity has become a global epidemic. Britain is the number one country with the most cases of obesity in children, with 36% followed by Spain with a prevalence of 27%. Riskesdas 2013 data for children aged 6-12 years is very high at 18.8%. Obesity in children decreases the level of intelligence because the activity and creativity of the child decreases and tends to be lazy due to being overweight. Physical activity affects the risk of obesity in children. The purpose of this study was to determine the relationship of physical activity with obesity in elementary school students of Bengkalis N 1 city in 2017. This study uses a cross sectional design. The sample is 65 respondents. The sampling used is Simple Random Sampling. Data collection using questionnaires and stages of analysis that is univariate and bivariate analysis using the Chi Square test with SPSS 20.0 program. Results of Univariate Analysis of respondents 'characteristics consisted of students' age and gender. The majority of respondents aged 11 years are 33 respondents (50.8%) and the minority of respondents 12 years is 32 (49.2%). The majority of male respondents were 41 respondents (63.1%) and female respondents were 24 students (36.9). The majority of light respondents were 43 people (66.2%) and students with heavy physical activity were 22 people (33.8%). The results of the bivariate analysis of 65 students who had mild physical activity were not obese as many as 24 students (55.8%) and were obese as many as 19 students (95.5%) as well as from 22 students whose physical activity was not obese as many as 21 students (44, 2%) and obese as many as 1 student (4.5%). Statistical test value of p value = 0.001, meaning that there is a relationship between physical activity and obesity, the value of PR = 16.625 with 95% CI 2.047-135.008. It is suggested to the school to encourage the monitoring of nutrition of school children to monitor the growth and development of nutritional status. Through the School Health Efforts Program (UKS) that already exists. It is re Keywords: Physical Activity, Obesity, School Children, Parents' Income, Students commended for school children to frequently do activities and exercise regularly